"Wounded History: A Reading of Edwidge Danticat's Fiction" - Šesnić, Jelena (Array, 2006)
The contemporary Haitian American writer Edwidge Danticat appropriates in her fiction representational models observable also in so-called minority, post- or neo-colonial writing, which bears comparison to the dynamics of trauma as laid out in contemporary cultural theory based on the revision and rereading of Freud's texts (especially by Laplanche, Caruth, Felman). Drawing on Danticat's fictional texts, such as the novels _The Farming of Bones_ (1998) and _Breath, Eyes, Memory_ (1994), and a short story collection _Krik? Krak!_ (1995), the article suggests indispensable links between the project of articulating traumatic events underlying collective, but unrecognized and so-far unrecorded, history, and the projects of bearing witness and carrying on the memory of an event. This conjunction is crucial for the articulation of collective, group history, and finds its embodiment in the hybrid form of historiographic metafiction and testimonial writing, and the ultimate impossibility of transposing the traumatic into the narrative (_The Farming of Bones_, _Krik? Krak!_). The other line of argumet tries to foreground the impact of structuring or base trauma as it interferes with the working-through and the transposition of a personal trauma into a coherent narrative of one's Bildung (_Breath, Eyes, Memory_). Still, these impasses mark a significant cultural intervention launched by Danticat and other similarly positioned authors in order to account for and bear witness to a history that articulates itself as an impossible, because traumatic, narrative.